Obesity-linked insulin resistance in children – an emerging problem: The EarlyBird Study (31) - Jeffery, AN; Metcalf, BS; Hosking, J; Voss, LD; Wilkin, TJ (International Diabetes Nursing, 2006)
Abstract Once virtually unheard of in adolescents and children, type 2 diabetes is rapidly becoming a significant paediatric problem. However, insulin resistance may precede the onset of diabetes by several years, and may be acquired early in life, when it is potentially reversible. The EarlyBird Study is following a group of healthy young children as they grow, aiming to establish why some children, but not others, will go on to develop insulin resistance. A total of 300 children and their parents were recruited into a prospective cohort study at the age of five years (2000/2001). Annual measures include height, weight, body composition, physical activity, resting energy expenditure, blood pressure, fasting insulin, glucose and lipids. Insulin resistance is calculated by HOMA-IR. Annual follow up is planned for twelve years, until the children are aged 16 years. Results in this paper are reported on the first four study years (children aged five to eight years): (1) The proportion of overweight and obese children rose with age, reaching almost one in five children at age eight. (2) Relationships between BMI and insulin resistance were evident from five years old, and strengthened over time, reaching a correlation value of r=0.51 (p<0.001) in eight-year-old girls. (3) Boys had a higher resting energy expenditure than girls. (4) Relationships between physical activity and metabolic health were inconsistent and varied with age and gender. This study presents evidence that excess weight is a key factor in early development of insulin resistance. EarlyBird is unique in its longitudinal design, which will help determine what combination of factors drives the development of childhood insulin resistance, their relative contribution and, importantly, how that contribution changes as children grow and mature.